Bacterial resistance to carbapenems in terms of public health - Skrzypek, Kinga; Malm, Anna (Polish Journal of Public Health, 2012)
The latest data confirm that the number of patients infected with resistant bacteria steadily increases, and the resistance of bacteria to antibiotics has become a global problem, one of the most important public health threats. In times when new medicines, such as antimicrobials, are not introduced onto the market, it is necessary to protect those already available. It can be done through the actions involving the rationalization of antibiotic therapy rules. Beta-lactam antibiotics, including carbapenems, so-called last resort medicines, take up a special place in the antibiotic therapy. The emerging new resistance mechanisms to carbapenems in bacteria with high potential for proliferation pose a real threat not only for health but especially for life of patients infected by multi-drug-resistant bacterial pathogens.